Hematoma extradural no idoso - Pereira, Carlos Umberto (1999)
O hematoma extradural tem sido cada vez mais freqüente no idoso. Nessa faixa etária, a queda da própria altura é a principal causa. A tomografia computadorizada é o principal meio de diagnóstico. O prognóstico encontrase diretamente relacionado ao escore na escala de coma de Glasgow à admissão e à presença de lesões intracranianas associadas._________________________________________________________________________________________ ABSTRACT: Extradural hematoma in the elderly has become much common. It is reported a series of nine patients older than 60 years with extradural hematoma. Falls were the main cause of the hematomas. Computed tomography was the procedure of choice for diagnosis. The prognosis was related to the Glasgow Coma Scale score presented by the patients at admission, to the associated intracranial lesions and systemic diseases.